Introduction (Itinera, 2017)
The issue starts from an international conference on the theme The Theatre and the five Senses. Theories, Aesthetics and Dramaturgies, held in Paris on June 13th and 14th 2016. The conference was part of a three-year international research project that comprises three European universities and different cultural and theatrical institutions from three countries (Italy, France, Romania). As the title of the conference indicates, the focus of this issue is the role that the senses play in the theater, in different cultural contexts and in different periods.